INTEGRITAS INTELECTUAL, EMOTIONAL, AND SPIRITUAL QUOTIENT DALAM PEMBENTUKAN NAFSUL MUTHMĀINNAH UNTUK MEWUJUDKAN KOMUNIKASI QUR`ANI - Roiyani Roiyani; Kusmawati Hatta (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2023)
A spiritual servant of Allah will become quiet souls by integrating SQ in his Nafs as the existence of divine light that is embedded in his Soft Heart, this will be realized by the existence of IQ awareness, while EQ awareness is a link between IQ and SQ. This study uses a qualitative method approach, with discourse analysis techniques and text interpretation. This method analyzes the process of a meaning contained behind the information contained in the Koran. The verses that explain the existence of IESQ in Nafs are found in [QS. Al-Qiyamah: 2], [QS. Al-Fajr: 27-28], [QS. ar-Ra'd:28], [QS. al-Jatsiyah: 5] and [HR. Muslim]. while the verses explaining the integration of the IESQ through the Quranic Communication Psychology process are contained in [QS. An-Nisa: 9], [QS. Al-Ahzab: 32], [QS. An-Nisa: 63], [QS. Al Isra': 23], [QS. Thaha: 43-44] and [QS. Al Isra': 28]. The results of the analysis of these verses are that Nafs is a container for sharing information and knowledge that has the characteristics of Resentment, Despicable and Peaceful. 'Aqal is the potential of the soul that has the ability to process information so that it becomes knowledge. While the process of delivering messages or information by applying the principles of Quranic Communication Psychology